Study of Technological Parameters of Pyrolysis of Waste Tires under Static Load - Markina, L.M.; Kryva, M.S. (Science and Innovation, 2024)
Introduction. Disposal of waste tires is a pressing problem in our country, since their amount has been constantly increasing. Inadequacy of the existing methods for thermal waste tire utilization has given rise to the necessity of developing an advance technology for their pyrolysis combined with static load. Problem Statement. Since no data on specific features of work process are available, this complicates the adjustment works and implementation of waste tire utilization by thermal decomposition under static load in industrial conditions. The determination of specific features of waste tire destruction in the reactor under static load is a relevant problem to be solved. Purpose. To determine the physical parameters of waste tire destruction in the pyrolysis reactor, under static load. Materials and Methods. To assess the effectiveness of the proposed method a series of experiments have been carried out. It includes the conventional pyrolysis of grinded waste tires in the reactor and tire pyrolysis under static load. Using COMSOL Multiphysics program, the physical parameters of vertical pyrolysis reactor filled with tires under temperature effect and static compression have been studied. Results. Diagrams that show thermal conductivity and distribution of temperature field inside the pyrolysis reactor in the case of compaction of processed products have been built using the method of end elements and solution of differential thermal conductivity equation. The time of tire stay in the reactor has been estimated as 7.8 hours. Optimal pressure on tire, which is required for maximum compaction has been determined. Conclusions. Raising performance of the plant for waste tire utilization by introducing static load into the process technology for multi-loop circulation pyrolysis has been substantiated. The use of static load has been shown to be an effective method, as it leads to an increase in the thermal conductivity coefficient of waste tire mass in the reactor and, consequently, a more even temperature distribution in the compacted tire mass.